Structure and properties of flame-sprayed poly(ethylene-co-vinyl alcohol) copolymer coatings - (:unkn) unknown (WILEY, 2004)
Powder coatings formed by flame spraying are being used in industrial applications. The resistance of plastics and their composite materials to chemicals, solvents, and atmospheric conditions and their high impact strength even at low service temperatures increase the importance of plastic and plastic-based coatings. In this study, an ethylene vinyl alcohol copolymer powder was coated via flame spraying with gases of oxygen and acetylene. The bond strengths and microstructures of the coatings were determined with tensile testing, scanning electron microscopy, and Fourier transform infrared. The bond strengths of the coatings were determined according to ASTM C 633. Oxidizing, carburizing, and neutral flames were used. The bond strengths were lower for the oxidizing and carburizing coatings than for the neutral flame coatings. The results indicated that during the flame-spraying process, the composition, gas, spraying distance, and coating thickness were important factors in the coating bond strength. (C) 2004 Wiley Periodicals, Inc.
Keywords: coatings; FT-IR; plastics; strength; structure